Interlanguage In Error Analysis Study - Basturi Hasan (Universitas Bandar Lampung, 2010)
Interlanguage theory is naturally a constantly evolving theory, having changed considerably since its initial formulation. It is, therefore, not an easy task to produce an accurate account of the theory. The aim of this article is basically to provide a brief and composite account of the interlanguage theory. In so doing, some crucial issues are accordingly viewed: (1) error analysis, (2) stages of interlanguage development, (3) Interlanguage transfer, (4) fossilization, (5) input hypothesis, (6) and pidginization fossilization, I ginization as well. There is in fact considerable disagreement about how best to characterize the nature of an interlanguage system. Nevertheless, this principle is able to account for insights provided byform-function analysis.